If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(4x + -3) + 4(3x + 7) = 0 Reorder the terms: 9(-3 + 4x) + 4(3x + 7) = 0 (-3 * 9 + 4x * 9) + 4(3x + 7) = 0 (-27 + 36x) + 4(3x + 7) = 0 Reorder the terms: -27 + 36x + 4(7 + 3x) = 0 -27 + 36x + (7 * 4 + 3x * 4) = 0 -27 + 36x + (28 + 12x) = 0 Reorder the terms: -27 + 28 + 36x + 12x = 0 Combine like terms: -27 + 28 = 1 1 + 36x + 12x = 0 Combine like terms: 36x + 12x = 48x 1 + 48x = 0 Solving 1 + 48x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 48x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 48x = 0 + -1 48x = 0 + -1 Combine like terms: 0 + -1 = -1 48x = -1 Divide each side by '48'. x = -0.02083333333 Simplifying x = -0.02083333333
| X/8+11=42 | | 15(y+2)=60 | | 3+2(x-1)=9x+4 | | 2x+2=-2(x+7) | | 200+0.15x=332 | | n+17=12 | | 8x+5=5x-7 | | 4x-4=4x-1-2 | | 6(3x+2)+5(4x+3)= | | 2x+3y=9.5 | | 5(x+7)=70 | | 108=473+23h | | 6-p2/8=-4 | | x-9+4x+5+5x-=50 | | 19x+29=105 | | 100(y^3z^2/5x)^2 | | 7x+5=2(4x+3) | | .5x-3.=.2x-.5 | | -188-7x=8x+17 | | (-6-x)/(3x-12)=0 | | 4/9+3/7 | | (x-5)*(1/2)-(2*x-1)*(1/3)=6 | | h+1/4h=35 | | 64d^2-36/8d+6 | | x+7/3=10 | | 64d^2-36/8d | | 1/3+5/12x-2=62/3 | | x^4+4x^3-19x^2-46x-1200=0 | | 2k^2-(12k+1)x+12=0 | | 8x5/2-88=0 | | tanx=-0.4 | | 3x+4+x=4x+1+3 |